Determination of optimum performance liquid glass of magnetization mixtures with liquid glass - Курын, Марина Григорьевна (Technology audit and production reserves, 2011)
The article describes the results of studies on the effect of the module and the density of liquid glass surface tension. It is shown that to improve the processing of liquid glass, use the following optimum characteristics of the liquid glass: Module 2,86 and density 1,45.